Hubungan Manajemen dengan Perkembangan Anak Usia Dini di TK Pertiwi II Sumatera Barat - Desriliwa Ade Mela; Dasril Davidra; Afni Tania (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Early childhood development is one thing that needs to be considered by all parties, both parents at home and also teachers at school, because good development certainly requires good processes and management where it will affect other aspects of a child's learning in its growth and development. The purpose of this study is first to describe the management carried out by Pertiwi II Kindergarten II on their students, secondly to describe early childhood development in Pertiwi II Kindergarten West Sumatra. In this study the approach used is a descriptive qualitative approach. The qualitative approach aims to explore the phenomena that occur in the object of research in detail and then interpreted descriptively in the form of words and language. The data sources in this research were obtained from school principals, teachers and students. Then the data obtained was collected through observation, interviews and documentation. The results of this study indicate that the West Sumatra Pertiwi II Kindergarten school has implemented a good management system such as creating a conducive school environment for early childhood, the learning methods used have also been effective and provide motivation to children in the classroom. This can help for early childhood development, both in terms of moral and religious development, social and emotional development as well as children's cognitive development.